IMPROVING THE STUDENTS READING COMPREHENSION THROUGH SCHEMATA TEACHING TEHNIQUE AT THE EIGHT GRADE OF SMP NEGERI 8 SELAYAR - Andi Irwin Maulana; Nurdevi Bte Abdul; Muh. Arief Muhsin (FKIP Unismuh Makassar, 2021)
Reading is challenging skill for students, where they have to comprehend the content of the text and identify the component of comprehension level. Dealing with this challenging this research aims to prove whether the Schemata Teaching Technique can improve the students’ reading comprehension. The research strategy utilized is classroom action research; it is conducted in two cycles. Each cycle is conducted in four gatherings. Each cycle comprises of planning, acting, observing, and reflecting. The information are taken from the occasion, archives and witnesses. The result of the inquire about appears that the way to move forward English students comprehension is by expanding their reading dominance utilizing schemata procedure where the students can do more works out which in a roundabout way too increment their comprehension in reading, and the result of post-test is way better than in pre-test. The mean score of pretest 67.74 to 78.61 in posttest cycle I, the mean score of pretest 71.17 to 80.52 in posttest cycle II. The percentages of exhaustiveness of each cycle also show the improvement, with 10.87% in first cycle, 9.35% in second cycle. The researcher suggests to the teachers especially English teachers to be more inventive to make a modern method in learning English uncommonly reading process. The analyst also concludes that educating English through schemata teaching technique can improve the students’ reading comprehension of the eighth grade students of SMP Negeri 8 Selayar.